Partnership for Market Readiness - Costa Rica Program : Program Alignment and Achievements - Partnership for Market Readiness (World Bank, Washington, DC, 2021)
Costa Rica ratified the United Nations Framework Convention on Climate Change (UNFCCC) in 1994 and has since developed and implemented national climate policies in accordance with its principles, primarily through the Ministry of Environment and Energy (MINAE) and its institutional structures. Early actions, together with the establishment of climate-specific policies, earned Costa Rica a place in the Partnership for Market Readiness (PMR), a multi-donor trust fund within the World Bank that supports participating countries to prepare and implement climate change mitigation policies including carbon pricing instruments in order to scale up greenhouse gas (GHG) mitigation. This document presents an overview of the program of technical activities implemented with grant resources and explains its relevance and integration into Costa Rica’s broader policy agenda. This document presents first an overview of the program and its alignment with Costa Rica’s ambitions and positions with regards to climate action. The document closes with insights and lessons from implementing the program.